Pengaruh Firm Size, Growth Opportunity, Liquidity dan profitability Terhadap Struktur Modal Perusahaan ( Studi Kasus pada Perusahaan Manufaktur "Food and Beverages" di Bursa Efek Indonesia Tahun 2011- 2013) - Sari, Febrianita Intan, Dra. Wafiatun Mukharomah, M.M (2015)
The purpose of this study was to test the effect of Firm Size, Growth Opportunity, Liquidity and Profitability of the capital structure in manufacturing. To test the effect of Firm Size, Growth Opportunity, Liquidity and Profitability together to capital structure in manufacturing. Population in this study are all food and beverages companies listed in Indonesia Stock Exchange as many as many 20 companies whereas the sample selection is based on purposive sampling methode. The company published financial statements as of 31 December for 2011-2013. T test analysis result obtained by the variabel Size, Growth, and Liquidity has no effect on the capital structure. Profitability has the effect of capital structure and F test result obtained Fhitung > Ftabel, then Ho is reject, meaning jointly variabel Size, Growth, Liquidity and Profitability together on the capital structure. The model used in this study is Fit and test analysis result are known coefficient of Determination adjusted R square of 0,456. This shows that the variation of the capital structure can be explained by the variable Size, Growth, Liquidity and Profitability of 45,6% while the rest is explained 54,4% influenced by other factors beyond the variables studied.